Advancing E-commerce Smart-PLS as a Catalyst for Improved Online Shopping Services - Alwiyah; Victorianda; Bennet, Daniel (Pandawan Sejahtera Indonesia, 2024)
In the fast-paced world of e-commerce, the adoption of advanced methodologies and technologies is vital to address the increasing demands and challenges of online shopping services. This paper examines the transformative impact of Partial Least Squares Structural Equation Modeling (Smart-PLS) on e-commerce. Smart-PLS is a powerful tool that offers a robust framework for analyzing and enhancing various aspects of e-commerce, such as customer experience, service quality, and business performance. This study explores how Smart-PLS facilitates a data-driven decision-making approach, resulting in better user experiences, optimized supply chains, and improved business strategies. The abstract underscores the importance of Smart-PLS as a revolutionary tool in the e-commerce sector, enabling businesses to adapt, innovate, and succeed in the digital marketplace. It highlights the potential of Smart-PLS to shape the future of online shopping services and stresses the necessity of its adoption for maintaining competitiveness in the ever-changing e-commerce landscape.